2012
DOI: 10.5851/kosfa.2012.32.6.718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Addition of Tomato Powder on Colour, Antioxidant, and Antimicrobial Traits of Pork Jerky during Storage

Abstract: The aim of this study was to investigate the effects of the addition of tomato powder [1.0% (T1), 1.5% (T2) and 2.0% (T3)] on pork loin jerky with aerobic package during storage at room temperature. The T3 sample showed lower (p<0.05) pH value and higher (p<0.05) water activity than the control during storage. Total plate counts of treated samples (≥1.20 Log CFU/g) were significantly (p<0.05) lower than the control (1.46 Log CFU/g) during storage. With the increase of the tomato powder concentration the lightn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…However, the increase in LE concentration had a significant effect on the inhibited water activity in the jerky during the storage period (p<0.001). Similar results were reported by Kim et al (2012) , who showed that the moisture content and water activity of pork jerky decreased during storage, leading to a tough texture of jerky during distribution and storage. Additionally, Choi et al (2007) had reported that water is diffused and dehumidified from the products in packaging; therefore, moisture content and water activity of products may decrease during storage.…”
Section: Resultssupporting
confidence: 89%
“…However, the increase in LE concentration had a significant effect on the inhibited water activity in the jerky during the storage period (p<0.001). Similar results were reported by Kim et al (2012) , who showed that the moisture content and water activity of pork jerky decreased during storage, leading to a tough texture of jerky during distribution and storage. Additionally, Choi et al (2007) had reported that water is diffused and dehumidified from the products in packaging; therefore, moisture content and water activity of products may decrease during storage.…”
Section: Resultssupporting
confidence: 89%
“…This implies that adding humectants to jerky will not affect the reduction of harmful bacterial growth or the avoidance of spoiling. Some researchers have mentioned that the reduction of pH in jerky could be due to a low pH value of adding humectants ( Kim et al, 2012b ) or containing organic acids in humectants ( Kim et al, 2010b ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the yellowness (b*) was found to increase significantly during the storage periods. Similarly, Kim et al [27] revealed that kiwi-tenderized pork jerky showed a greater yellowness (b*) value.…”
Section: Color Ph and Tbarsmentioning
confidence: 90%
“…Bromelain, a proteolytic enzyme found in pineapple, assists in the digestion of protein-rich food products [26]. In addition, lycopene from tomatoes may enhance the storage quality and color of meat products [27].…”
Section: Introductionmentioning
confidence: 99%